«A SYSTEMATIC APPROACH TO THE ANALYSIS OF PARADIGMATICS AND SYNTAGMATICS» (Scientific journal of the Fergana State University, 2024)
This article is devoted to the study of a systematic approach to the analysis of linguistic phenomena, such as paradigmatics and syntagmatics. The work examines the relationship between paradigmatics (selecting elements from a set of possible ones) and syntagmatics (combining elements into a sequence). The methodology of system analysis, based on the principles of systems thinking and structural analysis, is considered. The article includes theoretical aspects and practical examples of applying a systems approach to the analysis of language structures, which allows for a deeper understanding of the organization of language as a system.